RANCANG BANGUN SISTEM INFORMASI E-COMMERCE PARFUM BERBASIS WEBSITE - Yudha Muhammad,; Deddy Gusman,; Aris Fiatno, (Jurnal Inovasi Teknik Informatika, 2024)
The rapid change in information technology has transformed our way of doing activities, especially in the business and e-commerce sectors. E-commerce, the activity of buying, selling, and marketing goods and services through electronic systems, plays a significant role. One of the products sold in e-commerce is perfume, a fragrant liquid that boosts confidence and leaves a certain impression. Currently, the sales process in some stores in Bangkinang is still manual, where consumers have to visit the stores directly to make purchases or simply to view the available products, and there is a lack of detailed information about the perfumes. Difficulty in reaching consumers and challenges for consumers to determine the desired price due to various variations such as brands and qualities. The aim of this research is to design and develop a web-based perfume buying and selling information system using PHP with the CodeIgniter framework to help consumers easily find perfumes and facilitate online transactions. The method applied in developing the system is the SDLC (System Development Life Cycle) model with a waterfall approach. The result of this research is an information system for buying and selling perfumes made using the PHP programming language and the CodeIgniter Framework. This system is designed using UML (Unified Modeling Language), and Usability Testing and Blackbox Testing as system testing methods.